Assessment in Indonesian Higher Education: Developing a Reading Comprehension Test for English Students - Masduqi, Harits; Fatimah, Fatimah (International Research-Based Education Journal, 2022)
This paper describes the processes of designing, administering, and evaluating a reading comprehension test for intermediate–level students who have taken a General English course at the English language centre of an Indonesian university. Using R&D method, the writers developed the test which contains two authentic texts. The first text is It isn’t a Rehearsal, You Know, written by Ray Connolly and the second text is Ageing around the World, written by Timothy Johnson. The reading comprehension test is a part of summative assessment which is aimed to measure the students’ ability to comprehend two different types of texts based on skimming, scanning, and vocabulary skills. Having done the processses of developing the reading test, the writers have some important points to revise including level of difficulty of the texts, the test organisation, and the reading skills tested. The writers recommend that understanding and practicing appropriate procedures to develop a reading comprehension test is not only crucial for English teachers to measure their students’ reading skills, but also necessary for their professional development.